Exploring Refinement Strategies for Single Housing of Male C57BL/6JRj Mice: Effect of Cage Divider on Stress-Related Behavior and Hypothalamic-Pituitary-Adrenal-Axis Activity - Buckinx, An; Van Schuerbeek, Andries; Bossuyt, Jo; Allaoui, Wissal; Van Den Herrewegen, Yana; Smolders, Ilse; De Bundel, Dimitri (Frontiers in Behavioral Neuroscience, 2021)
Introduction: Single housing of laboratory mice is a common practice to meet experimental needs, or to avoid intermale aggression. However, single housing is considered to negatively affect animal welfare and may compromise the scientific validity of experiments. The aim of this study was to investigate whether the use of a cage with a cage divider, which avoids physical contact between mice while maintaining sensory contact, may be a potential refinement strategy for experiments in which group housing of mice is not possible. Methods: Eight-week-old male C57BL/6JRj mice were single housed, pair housed or pair housed with a cage divider for four (experiment 1) or ten (experiment 2) weeks, after which we performed an open field test, Y-maze spontaneous alternation test, elevated plus maze test, an auditory fear conditioning task, and assessed responsiveness of the hypothalamic-pituitary-adrenal (HPA) axis. Results: Housing conditions did not affect body weight, exploratory activity, anxiety, working memory, fear memory processing or markers for HPA-axis functioning in either experiment 1 or experiment 2. There was an increased distance traveled in mice housed with a cage divider compared to pair housed mice after 4 weeks, and after 10 weeks mice housed with a cage divider made significantly more arm entries in the Y-maze spontaneous alternation test. Conclusion: Taken together, our study did not provide evidence for robust differences in exploratory activity, anxiety, working memory and fear memory processing in male C57BL/6JRj mice that were single housed, pair housed or pair housed with a cage divider.